Adequate Funding as Panacea for Students’ Loan Programme Implementation and Sustainability in Nigeria (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper examines the significance of adequate funding as a panacea for Nigeria’s student loan programme for tertiary education students. As a position paper, it relies on secondary data collected from print and online publications. The paper argues that adequate funding is critical to the effective implementation and sustainability of the student loan programme in Nigerian tertiary institutions. It emphasizes that a well-funded programme would ensure the achievement of its objectives, including equitable access to education for students from low-income backgrounds, efficient loan disbursement processes, and improved administrative capacities. Furthermore, adequate funding would facilitate the recruitment of qualified staff, effective training for loan administrators, and the acquisition of necessary technological tools to enhance service delivery. The discussion highlights that without sufficient financial backing, the programme risks encountering operational bottlenecks, such as delays in loan disbursements, poor loan recovery rates, and diminished trust in its long-term viability. By examining global best practices, the paper underscores that creating special funding sources, such as education bonds or partnerships with financial institutions, could significantly strengthen the programme’s foundation. Additionally, fostering accountability and transparency in fund allocation and utilization is identified as a critical factor for success. The paper concludes that funding plays a pivotal role in determining the overall success of the student loan programme and its ability to transform tertiary education in Nigeria. The study recommends among other things that the Federal Government of Nigeria should prioritize and allocate sufficient funds to the student loan programme to ensure that financial constraints do not hinder its operations and effectiveness.